1988
DOI: 10.1007/bf00381492
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder strain in keyboard workers and its alleviation by arm supports

Abstract: Keyboard work consists mostly of dynamic contractions of the small muscles of the forearms and hands. This is accompanied by continuous activity in the arm, shoulder and neck muscles keeping the head and hand in the correct position. Eliminating the weight from the arm by means of support and the position of the arms influences the electrical activity of shoulder muscles when working at a keyboard. We studied the influence of elbow angle; as well as that of different arm supports, on electrical activity of upp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…Aaras et al (1998) and Visser et al (2000) report decreased UT activity with the provision of forearm support. However, Cook et al (2004a,b), Erdelyi et al (1988) and Tepper et al (2003) found no difference in UT activity with forearm support. Differences in the nature of the supports and the nature of the tasks performed may have contributed to the differing results.…”
Section: Forearm Support and Muscle Activitymentioning
confidence: 93%
“…Aaras et al (1998) and Visser et al (2000) report decreased UT activity with the provision of forearm support. However, Cook et al (2004a,b), Erdelyi et al (1988) and Tepper et al (2003) found no difference in UT activity with forearm support. Differences in the nature of the supports and the nature of the tasks performed may have contributed to the differing results.…”
Section: Forearm Support and Muscle Activitymentioning
confidence: 93%
“…Crosssectional studies have shown that pat ients with trapezius myalgia use their muscles at a higher static level than healthy subj ec ts do (3)(4)(5). Subjects who ha ve suffered mu scle pain on a previou s occasion, but not during a recording sess ion, have also shown a higher static electromyographic (EMG) level than subj ec ts without sy mptoms (6) .…”
mentioning
confidence: 99%
“…Recording MVC would have increased muscle activity potentially influencing data recorded at rest, during ALF and AKE [48] . Within a data collection session where no individual changes to the configuration of the EMG set-up (electrode placement, amplification, filtering) has taken place and whilst under constant temperature and humidity conditions EMG data does not need to be normalised against a MVC to be interpreted [49][50] .…”
Section: Emg Data Collection and Filtermentioning
confidence: 99%